2021
DOI: 10.1371/journal.pone.0259583
|View full text |Cite
|
Sign up to set email alerts
|

Gendered health, economic, social and safety impact of COVID-19 on adolescents and young adults in Nairobi, Kenya

Abstract: Background Infectious disease outbreaks like COVID-19 and their mitigation measures can exacerbate underlying gender disparities, particularly among adolescents and young adults in densely populated urban settings. Methods An existing cohort of youth ages 16–26 in Nairobi, Kenya completed a phone-based survey in August-October 2020 (n = 1217), supplemented by virtual focus group discussions and interviews with youth and stakeholders, to examine economic, health, social, and safety experiences during COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 29 publications
4
21
0
Order By: Relevance
“…A mixed-methods assessment of health effects of Covid-19 in Kenya found significant reductions in outpatient visits and -in keeping with the worsening community safety and increases in domestic violence reported in our study -an increase in sexual violence cases reported (21). The gendered aspects of the impacts extend beyond violence, however, as we found and as has also been noted by others in terms of the socio-economic impacts disproportionally affecting women and girls (22,23).…”
Section: Key Findings In Contextsupporting
confidence: 89%
“…A mixed-methods assessment of health effects of Covid-19 in Kenya found significant reductions in outpatient visits and -in keeping with the worsening community safety and increases in domestic violence reported in our study -an increase in sexual violence cases reported (21). The gendered aspects of the impacts extend beyond violence, however, as we found and as has also been noted by others in terms of the socio-economic impacts disproportionally affecting women and girls (22,23).…”
Section: Key Findings In Contextsupporting
confidence: 89%
“…It is past curfew, you can’t leave the house. So, he might do anything to you (Young woman, age 15–19 years) 42…”
Section: Resultsmentioning
confidence: 99%
“…Because before, the violence was there so much but nowadays it is hard to meet, and when you meet it is hard. So, if there is any violence which comes up, you break up (Young woman, age 15–19 years) 42…”
Section: Resultsmentioning
confidence: 99%
“…More details on the sample and study procedures are outlined elsewhere. 28 All the participants provided informed consent prior to be enrolled to the study.…”
Section: Methodsmentioning
confidence: 99%